Allostatic Dysregulation of Natural Reward Processing in Prescription Opioid Misuse: Autonomic and Attentional Evidence - Garland, Eric L. (Biol Psychol, 2015)
Chronic pain patients who misuse prescription opioids may suffer from allostatic dysregulation of natural reward processing. Hence, this study examined whether prescription opioid misusers with chronic pain (n = 72) evidenced decreased natural reward responsiveness relative to non-misusers with chronic pain (n = 26). Subjects completed a dot probe task containing pain-related, opioid-related, and natural reward stimuli while attentional bias (AB) scores and heart rate variability (HRV) responses were assessed. Compared to non-misusers, misusers evidenced significantly more attenuated HRV responses to opioid, pain, and natural reward cues presented during the dot probe task. These significant between-groups differences in HRV were largest during attention to natural reward cues, but became non-significant in a sensitivity analysis controlling for opioid dosing. In addition, non-misusers evidenced an AB toward natural reward cues, whereas misusers did not. Findings suggest that opioid misusers exhibit attentional and autonomic deficits during reward processing.